Technological, Environmental And Commercial Drivers For The Use Of Geopolymers In A Sustainable Materials Industry - Jannie S. J. van Deventer (The Minerals, Metals and Materials Society, 2006)
Geopolymers are novel engineering materials with the potential to play a highly significant role in the transformation of the construction materials and building products industry in the push towards sustainable development. These materials are formed by activation of industrial aluminosilicate waste materials such as coal ash or blast furnace slag with alkaline solutions. Geopolymers derived from coal ash can exhibit superior mechanical properties and chemical stability when compared to ordinary Portland cement (OPC). The use of waste-based geopolymers can also result in significant (up to 90%) reduction in carbon dioxide emissions when used in cement replacement applications. In addition to the formation of conventional pre-cast products, these high performance mineral binders are ideally suited to use in the encapsulation of mine tailings, immobilization of heavy metals and back-filling of mines due to their chemical stability and resistance to acid attack. A key attribute of geopolymer technology is the robustness and versatility of the manufacturing process; it enables products to be tailor-made from a range of raw material sources (waste and/or virgin) with specific properties for a given application at a competitive cost. Despite these key technical and environmental attributes, it is the ability to add significant value to coal ash or and/ or metallurgical slag waste streams which drives the commercial development and uptake of the technology.